Collateral costs: the effects of incarceration on the employment and earnings of young workers - Harry J. Holzer (Institute for the Study of Labor (IZA), 2007)
In this paper I review the empirical evidence on the effects of incarceration on the subsequent employment and earnings of less-educated young prisoners. In this discussion I include evidence from: 1) Employer surveys and audit studies of hiring; 2) Survey data (mostly from the NLSY79) and administrative data; and 3) state-level incarceration data linked to micro employment data for young black men. The strengths and weaknesses of each type of analysis are discussed as well. The preponderance of the evidence considered suggests that, all else equal, spells of incarceration do tend to reduce subsequent employment and earnings for those with criminal records.
Keywords: 330; Incarceration; employment; earnings; Straftäter; Jugendliche Arbeitskräfte; Erwerbsverlauf; Lohn; USA